Evaluating the Implementation Efforts of Sustainable Value Management Strategies in Northern Nigeria. - Mubarak Sadis, Aminu; Sani Usman, Kunya; Mohammed, Musa (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Value management (VM) has emerged as a valuable strategy in numerous countries for advancing sustainability objectives. The study was to evaluate the implementation of VM and its role in promoting sustainable building initiatives in northern Nigeria. The questionnaire was administered to 250 construction professionals, facilitating an in-depth exploration of VM practices in the country. Data analysis encompassed techniques such as exploratory factor analysis (EFA), alongside descriptive statistics including frequency analysis and measures of central tendency. The findings indicate that 64% of respondents demonstrated awareness of VM, indicating familiarity with its principles. However, a significant majority (85.3%) reported non-adoption of VM practices and lacked formal training in VM methodologies. EFA revealed five principal components characterizing VM activities: an information phase, functional assessment, creative exploration, evaluation procedures, and project development/presentation stages. This research contributes to the awareness and understanding of VM among building professionals, thereby facilitating cost optimization and bolstering sustainability endeavors within building projects, particularly in developing nations like Nigeria. Ultimately, the insights garnered from this study hold the potential to enhance building management practices by integrating key elements of VM, thereby ensuring efficient resource allocation and alignment with sustainability objectives.